Pengaruh Harga Diri Terhadap Motivasi Aktivitas Fisik Pada Ibu Rumah Tangga Dan Ibu Bekerja - Anggraeni, Poppy Dian; Alwi, M. Ahkam; Nur, Haerani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Regular physical activity has important benefits for physical and psychological health. After marriage, mothers have their own challenges in maintaining motivation for physical activity. This study aims to determine the influence of self-esteem on physical activity motivation in working mothers and housewives. The research method used is quantitative with a simple regression research design. This study uses accidental sampling to collect samples. The sample criteria used were mothers aged 19-55 years and still in marital status. A total of 237 respondents consisting of 138 working mothers and 99 housewives were involved in this study. Data was collected using a questionnaire scale shared via Google Forms. The results showed that the level of self-esteem and motivation for physical activity was in the moderate category. Regression analysis showed that self-esteem had no significant effect on physical activity motivation (r = 0.0775, p > 0.05. The results of the Independent Samples T Test hypothesis test showed a p value of 0.335 (>0.05), so it can be concluded that there is no difference in physical activity motivation between housewives and working mothers. In conclusion, this study showed that there was no effect of self-esteem on physical activity motivation in mothers and there was no difference in physical activity motivation in housewives and working mothers. Keywords: motivation for physical activity, self-esteem, housewife, working mother